2011
DOI: 10.1002/aic.12369
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of flow regimes of axisymmetric and planar opposed jets

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Dynamic behaviors of axisymmetric and planar opposed jets have been experimentally studied at 786 \ Re \ 6288. The flow patterns were investigated by a smokewire technique, and the smoke-wire photos were recorded by a high-speed camera. Different flow regimes of axisymmetric and planar opposed jets have been identified. Axisymmetric opposed jets exhibit axial quasi-periodic oscillations, stagnation point offsets, and steady states, while planar opposed jets exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…It must be pointed out first that the self-sustained chaotic oscillation in RIM is related to the confined boundary condition, [15][16][17][18][19] which is different to the low-frequency periodic oscillation of axisymmetric opposed jets with excitations. Second, current results can be used to explain the low-frequency irregular oscillations reported in the experiments 20,21 but absent in the simulation and stability analysis. 13,14 This discrepancy is due to the different boundary conditions, because the velocity inlet in the simulation is laminar and constant, while the flow fluctuations and other disturbance more or less exist in experiments.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It must be pointed out first that the self-sustained chaotic oscillation in RIM is related to the confined boundary condition, [15][16][17][18][19] which is different to the low-frequency periodic oscillation of axisymmetric opposed jets with excitations. Second, current results can be used to explain the low-frequency irregular oscillations reported in the experiments 20,21 but absent in the simulation and stability analysis. 13,14 This discrepancy is due to the different boundary conditions, because the velocity inlet in the simulation is laminar and constant, while the flow fluctuations and other disturbance more or less exist in experiments.…”
Section: Discussionmentioning
confidence: 95%
“…18,19 However, Stan and Johnson 20 have observed an irregular lowfrequency oscillation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) for two opposed water jets, and the corresponding values of St are in the range of 2-8. In our previous study, 21 we have also observed some axial irregular oscillations or quasiperiodic oscillations for unrestricted axisymmetric opposed jets occasionally, whose peak frequency is about 10 Hz and St is in the range of 0.01-0.07. It should be pointed out that the irregular oscillation or quasiperiodic oscillation result form the exterior disturbances such as the flow fluctuation or smoke-wires.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Much work has been done on the flow and turbulence characteristics of the flow field in coaxial impinging stream reactors [20][21][22][23][24]. Huai et al have studied drying and flow characteristics in a semicircular impinging stream reactor.…”
Section: Introductionmentioning
confidence: 99%